Magnetic reconnection along quasi-separatrix layers as a drivers of ubiquitous active region outflows - Baker, D. (2009)
Hinode´s EUV Imaging Spectrometer (EIS) has discovered ubiquitous outflows of a few to 50 km s-1 from active regions (ARs). These outflows are most prominent at the AR boundary and appear over monopolar magnetic areas. They are linked to strong non-thermal line broadening and are stronger in hotter EUV lines. The outflows persist for at least several days. Using Hinode EIS and X-Ray Telescope observations of AR 10942 coupled with magnetic modeling, we demonstrate that the outflows originate from specific locations of the magnetic topology where field lines display strong gradients of magnetic connectivity, namely quasi-separatrix layers (QSLs), or in the limit of infinitely thin QSLs, separatrices. We found the strongest AR outflows to be in the vicinity of QSL sections located over areas of strong magnetic field. We argue that magnetic reconnection at QSLs separating closed field lines of the AR and either large-scale externally connected or "open" field lines is a viable mechanism for driving AR outflows which are likely sources of the slow solar wind.